Cancer chromatin accessed. Issue 1 (January 2019) - Trenkmann, Michelle
A study inScience reports the genome-wide chromatin accessibility profiles across 23 cancer types from The Cancer Genome Atlas and notably increases the number of known gene regulatory elements.